Self-Efficacy and Tutorial Performance of First-Year Students in The Faculty of Medicine - Irsyad Muhammad Sumarna; Umatul Khoiriyah (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: PBL (Problem Based Learning) is a common learning method in medical faculty around the world. Tutorials are the main learning activity in PBL. Internal (self-efficacy) and external (learning model) factors affect student learning performance. This study aims to determine the relationship between self-efficacy and tutorial performance of first year students of the Faculty of Medicine, Islamic University of Indonesia.Method: This study used a quantitative method with a cross-sectional observational design. The research instruments used in the study were the General Self-Efficacy Scale (GSES) that had been adapted in Bahasa Indonesia and the tutorial activity score of Block 1.6 Endocrine and Reproductive Systems of the 2021 Competency-Based Curriculum (CBC).Result: There is a significant relationship between self-efficacy and tutorial performance (p0.05). There is a significant difference in tutorial performance based on gender, motivation to enter FK and participation in student organizations.Discussion: There is a relationship between self-efficacy and student activeness in tutorial performance. However, tutorial performance is also related to several confounding variables, which are gender